ssessment of the Role of Women Participation in Community Development in Benin Metropolis: S. E. Omiunu, Airhiavbere Osaro Friday (PJDOL, 2023)
This paper investigated the role of women participation in community development in Benin Metropolis. A simple survey research design was employed to explore the issue. A 15 item questionnaire supplemented with oral interview sessions provided the data used for the study. The study involved 100 randomly selected women in Benin metropolis. The sample was drawn from across four communities within Benin metropolis